Employee Performance and The Influence of Leadership Style and Compensation - Sri Hamdyani; Andi Syarifuddin; Nurhani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to determine the influence of Leadership Style and Compensation on employee performance in South Sulawesi Province's public works and spatial planning offices. This type of research is quantitative research. The data used is secondary data. The sample used in this study was 62 consisting of 162 populations registered at the Office. Data analysis used Explanatory Research and Multiple Regression Analysis techniques assisted by SPSS for data analysis. The results of this study indicate that partially Leadership Style has a positive and significant influence on Employee Performance, Compensation has a positive and significant influence on Employee Performance, and Leadership Style and Compensation simultaneously have a positive and significant influence on Employee Performance.